Conversion of 2-Amino-4-chloro-3-methylbenzenethiol into Bioactive Heterocycles Containing 1,4-Thiazine Nucleus: Phenothiazine Tranquillizers - Rathore, R.K.; Gupta, R.R. (Asian Journal of Chemistry, 2012)
A convenient synthesis of some heterocycles containing 1,4-thiazine nucleus is reported. It involves the condensation and oxidative cyclization of 2-amino-4-chloro-3-methylbenzenethiol with 2-mino/2, 6-dihalonitrobenzenes. The structures of the synthesized compounds have been characterized by the analytical and structural studied.